Depression and delayed tuberculosis treatment initiation among newly diagnosed patients in Botswana. Issue 7 (3rd July 2021) - Molebatsi, Keneilwe; Wang, Qiao; Dima, Mbatshi; Ho-Foster, Ari; Modongo, Chawangwa; Zetola, Nicola; Shin, Sanghyuk S.
ABSTRACT: Comorbidity of tuberculosis (TB) and depression may lead to delayed TB treatment initiation. A cross-sectional study was conducted between January and December 2019 to examine the association between depression and delayed TB treatment initiation among newly diagnosed TB patients in Botswana. We used the Patient Health Questionnaire-9 and the ZUNG self-rating anxiety scale to assess depressive and anxiety symptoms, respectively. Delayed TB treatment was defined as experiencing common TB symptoms for more than 2 months before treatment initiation. We used Poisson regression models with robust variance to assess the association between covariates and delayed treatment initiation. Majority of the enrolled 180 study participants were males (n =116, 64.4%). Overall, 99 (55%) were co-infected with HIV; depression and anxiety symptoms were reported by 47.2% and 38.5% of the participants respectively. The prevalence of delayed TB treatment was 42.6% and 18.8% among participants who indicated symptoms of depression and among participants without depression respectively. After adjusting for age, HIV status, gender and anxiety symptoms, depression was still associated with delayed TB treatment (adjusted prevalence ratio [aPR] = 2.09; 95% CI = 1.23–3.57). Integrating management of depressive symptoms during TB treatment may help in improving overall TB treatment outcomes.